Rosin: The Source and Production of Gum and Wood Rosin - Hercules Incorporated (1950)
General view of an exhibition display panels depicting the production of gum and wood rosin by the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Corporations; Chemical industry; Hercules Powder Company; Advertising; Advertising, Industrial; Gums and resins